Analisis Aktivitas Siswa dan Guru dalam Pembelajaran IPA Terpadu Kurikulum 2013 di SMP - Pradani, Devi Rakhma; Mosik, Mosik; Wiyanto, Wiyanto (UPEJ Unnes Physics Education Journal, 2018)
Science Learning in the curriculum of 2013 is developed as integrated learning not as a science discipline. Teaching and learning process consist of students and teacher activity. The purpose of this study is to know about the verbal activity from the teacher and student hands-on activity and the integration of learning material. This research was descriptive research. The subjects of the research were the students of class VIIIB, VIIIH and VIIF of SMP N 1 Bobotsari. The technique of data analysis is by making the transcript of ideo learning process. The result of the research is the description of student and teacher verbal activity, hands on activity, and integration of learning materials. Teacher's verbal activity is dominated by 62.34% of questions. The student's verbal activity is dominated by the answer statements of 69,44%. Average result of hands on activity was 33.12%. The integration of learning materials for class VIII B and VIII H has not shown the integration of Integrated Science, whereas for class VII F has shown the integrity of material from Integrated Science.